2020
DOI: 10.1097/nmd.0000000000001277
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Moral Injury Symptoms in Health Care Professionals

Abstract: This study examined the prevalence and predictors of moral injury (MI) symptoms in 181 health care professionals (HPs; 71% physicians) recruited from Duke University Health Systems in Durham, NC. Participants completed an online questionnaire between November 13, 2019, and March 12, 2020. Sociodemographic, clinical, religious, depression/anxiety, and clinician burnout were examined as predictors of MI symptoms, assessed by the Moral Injury Symptoms Scale–Health Professional, in bivariate and stepwise multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
61
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 50 publications
9
61
3
Order By: Relevance
“…39,40 Although the present study used a cross-sectional design that prevented causal inferences, spiritual-based interventions directed at moral injury have effectively reduced PTSD and other negative emotions among military personnel. 22,23 Likewise, Mantri and colleagues found in a sample of US healthcare professionals that moral injury was associated with significantly higher depression and anxiety, 18 as in the present study.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…39,40 Although the present study used a cross-sectional design that prevented causal inferences, spiritual-based interventions directed at moral injury have effectively reduced PTSD and other negative emotions among military personnel. 22,23 Likewise, Mantri and colleagues found in a sample of US healthcare professionals that moral injury was associated with significantly higher depression and anxiety, 18 as in the present study.…”
Section: Discussionsupporting
confidence: 77%
“…16 Spiritual beliefs may provide coping resources (cognitive, social) and rituals (confession, repentance) for dealing with moral transgressions. Studies have found that spirituality is inversely associated with moral injury in US veterans 17 and US healthcare professionals, 18 and it may help to moderate the effects of moral injury on PTSD symptoms or promote recovery when such difficulties emerge. 19 Spiritual beliefs, however, may also contribute to self-condemnation for failure to live up to the high moral standards advocated by religious bodies, thereby contributing to moral injuries.…”
Section: Spirituality Moral Injury and Mental Healthmentioning
confidence: 99%
“…When HCPs experience "burnout," as is so common today, MI may be the actual underlying cause (Kopacz et al, 2019;Talbot & Dean, 2018). Furthermore, MI has been associated with increased medical errors among HCPs during the COVID-19 pandemic (Mantri et al, 2021a;Wang et al, 2021). It may be difficult, however, to determine whether such medical errors are the result of MI or its cause (Curlin 2005;Stovall et al, 2020).…”
Section: Healthcare Professionalsmentioning
confidence: 99%
“…There are also several personal, behavioral, and situational factors that characterize the presence of MI in healthcare professionals. These include younger age (Mantri et al, 2021b;Wang et al, 2021), female gender (Wang et al, 2021), the unmarried (Wang et al, 2021), the divorced (Mantri et al, 2021b), those with lower religiosity (Mantri et al, 2021a(Mantri et al, , 2021b, Buddhist or Taoist religion (vs. no religion) (Wang et al, 2021), involvement in the care of COVID-19 patients (Mantri et al, 2021b;Wang et al, 2021), nurses (vs. physicians) (Mantri et al, 2021b), higher levels of burnout or emotional exhaustion (Mantri et al, 2021a(Mantri et al, , 2021bWang et al, 2020Wang et al, , 2021, and exposure to workplace violence (Wang et al, 2020(Wang et al, , 2021. As in studies of military personnel, depression and anxiety symptoms have been significantly correlated with MI in each of the studies above (except when controlling for HCP burnout).…”
Section: Healthcare Settingsmentioning
confidence: 99%
“…Moral injury has been reported in around a quarter of healthcare workers in some settings (3) though moral injury amongst essential workers in the UK, particularly during the Covid-19 pandemic, has not been described fully. Seeking staff experiences and views is, therefore, important so that any interventions can be tailored to need and are more likely to be successful.…”
Section: Introductionmentioning
confidence: 99%